Pseudogemmobacter bohemicus gen. nov., sp. nov., a novel taxon from the Rhodobacteraceae family isolated from heavy-metal-contaminated sludge - Suman, Jachym; Zubrova, Andrea; Rojikova, Katerina; Pechar, Radko; Svec, Pavel; Cajthaml, Tomas; Ulbrich, Pavel; Ridl, Jakub; Strnad, Hynek; Uhlik, Ondrej (International journal of systematic and evolutionary microbiology, 2019)
The creamy white to beige, aerobic, non-motile, ovoid to rod-shaped, Gram-stain-negative strain, Cd-10T, was isolated from heavy-metal-contaminated sludge from a decantation basin of a heavy metal processing factory based on its ability to tolerate CdCl2 in the cultivation medium. In the reconstruction of its phylogeny based on 16S rRNA gene sequences, strain Cd-10T clustered with species of the genera Gemmobacter, Xinfangfangia, Tabrizicola and Rhodobacter within the family Rhodobacteraceae. Its 16S rRNA gene sequence exhibited 96.32 % pairwise similarity to the type strain of Xinfangfangia soli, 95.3 % to that of Gemmobacter intermedius, followed by Tabrizicola fusiformis (95.10 %), Rhodobacter sediminis (94.88 %), Gemmobacter nectariphilus and Rhodobacter capsulatus (both 94.81 %). The major respiratory quinone was Q-10 accompanied by Q-9, the fatty acid profile consisted predominantly of C18 : 1ω7c, C18 : 0, C16 : 0 and C16 : 1ω7c, the major polar lipids were phosphatidylglycerol, phosphatidylmethylethanolamine, phosphatidylcholine and diphosphatidylglycerol. An analysis of the percentage of conserved proteins deduced from draft or complete genomic sequences of strain Cd-10T and representatives of its closest relatives suggested that strain Cd-10T is a member of a novel genus within the Rhodobacteraceae family for which we propose the name Pseudogemmobacter. Strain Cd-10T (=DSM 103618T=NCCB 100645T) is the type strain of Pseudogemmobacter bohemicus gen. nov., sp. nov., the type species of the genus Pseudogemmobacter gen. nov.
Keywords: Metals, Heavy; DNA bakterií; Phylogeny; Sewage; Rhodobacteraceae; techniky typizace bakterií; Sequence Analysis, DNA; zastoupení bazí; RNA ribozomální 16S; Base Composition; RNA, Ribosomal, 16S; sekvenční analýza DNA; DNA, Bacterial; mastné kyseliny; těžké kovy; odpadní vody; Phospholipids; fylogeneze; Czech Republic; Ubiquinone; Bacterial Typing Techniques; fosfolipidy; Česká republika; ubichinon; Fatty Acids